2015
DOI: 10.1016/j.jconrel.2014.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of beraprost sodium in nanoparticles: Analysis of sustained release properties, targeting abilities and pharmacological activities in animal models of pulmonary arterial hypertension

Abstract: Prostaglandin I2 (PGI2) and its analogues (such as beraprost sodium, BPS) are beneficial for the treatment of pulmonary arterial hypertension (PAH). The encapsulation of BPS in nanoparticles to provide sustained release and targeting abilities would improve both the therapeutic effect of BPS on PAH and the quality of life of patients treated with this drug. BPS was encapsulated into nanoparticles prepared from a poly(lactic acid) homopolymer and monomethoxy poly(ethyleneglycol)-poly(lactide) block copolymer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
(47 reference statements)
3
18
0
Order By: Relevance
“…Pitavastatin,(24) nuclear factor kappaB decoy, (25) imatinib, (26) prostacyclin analog, (27,28), fasudil, (29) and antimiRNA-145-incorporated NPs, (30) have been reported to be effective in animal models of PH (Table 1). In this review, we summarize results of recent studies using prostacyclin analog-incorporated NPs (27,28) and imatinib-incorporated NPs. (26) NF-kB, nuclear factor kappaB; PLGA, poly(lactide-co-glycolide); PEG-PLGA, poly-(ethyleneglycol)-PLGA;…”
Section: Nanoparticle-mediated Drug Delivery System (Nano-dds)mentioning
confidence: 99%
“…Pitavastatin,(24) nuclear factor kappaB decoy, (25) imatinib, (26) prostacyclin analog, (27,28), fasudil, (29) and antimiRNA-145-incorporated NPs, (30) have been reported to be effective in animal models of PH (Table 1). In this review, we summarize results of recent studies using prostacyclin analog-incorporated NPs (27,28) and imatinib-incorporated NPs. (26) NF-kB, nuclear factor kappaB; PLGA, poly(lactide-co-glycolide); PEG-PLGA, poly-(ethyleneglycol)-PLGA;…”
Section: Nanoparticle-mediated Drug Delivery System (Nano-dds)mentioning
confidence: 99%
“…Targeting PLCγ in DN [2] : Inhibitors of p38MAPK signaling Pathway [2,31] : Animal model study Beraprost Sodium: In investigational study Beraprost sodium enhanced lipid profile, blood glucose, 24 hour urinary protein p38MAPK signaling pathway is activated in diabetic kidney.…”
Section: Specific: Specific Inhibitor Nox 4 Isoformmentioning
confidence: 99%
“…Further study is needed to understand the beneficial effect of inhibiting pathway. Currently nanoparticles of Beraprost are tested in animal models with pulmonary hypertension [31] on similar lines it could be tested in DN.…”
Section: Specific: Specific Inhibitor Nox 4 Isoformmentioning
confidence: 99%
“…Higher accumulation and prolonged residence time in the pulmonary arteries. Effective against MCT-and hypoxiainduced pulmonary arterial remodeling and right ventricular hypertrophy [128] A C C E P T E D M A N U S C R I P T…”
Section: (Ii) Polymeric Nanoparticlesmentioning
confidence: 99%
“…Although the formulation was not tested in animal PAH model, it was suggested that nanoparticles could be potential carriers for targeted PAH therapy. Later, the same group developed beraprost loaded PLGA nanoparticles and tested in MCT-induced and hypoxia-induced mouse PAH model for their pharmacological activity [128]. Beraprost-loaded nanoparticles showed higher accumulation and prolonged residence time in the damaged pulmonary arteries.…”
Section: Accepted Manuscriptmentioning
confidence: 99%